2022
DOI: 10.1590/2526-8910.ctoao242731672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the professional clinical practice of occupational therapy

Abstract: Introduction A series of restrictive health care measures emerged limiting actions that include the work of occupational therapists and proposing adaptations to provide care to people who require it. Objective To identify the impact and adaptations in the care of Occupational Therapy clinical professionals due to the COVID-19 pandemic in Colombia. Methods Cross-sectional study that applies an online questionnaire in January-February 2021 to Colombian occupational therapists in clinical/hospital settings. Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…RTs either struggled with modifying their hands-on approach or considered virtual care an effective alternative. Overwhelmingly, virtual care was reportedly widely implemented as a mode of intervention delivery for rehabilitation services [51][52][53] with mixed responses [52,54]. Therefore, COVID-19 provided an opportunity to learn and potentially further develop models of virtual rehabilitation care [55], including adopting practical resources from established virtual rehabilitation programs [56].…”
Section: Discussionmentioning
confidence: 99%
“…RTs either struggled with modifying their hands-on approach or considered virtual care an effective alternative. Overwhelmingly, virtual care was reportedly widely implemented as a mode of intervention delivery for rehabilitation services [51][52][53] with mixed responses [52,54]. Therefore, COVID-19 provided an opportunity to learn and potentially further develop models of virtual rehabilitation care [55], including adopting practical resources from established virtual rehabilitation programs [56].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, there seems to be a problem of precarious employment and low pay among Colombian occupational therapists. For example, Moreno-Chaparro et al (2022) surveyed 382 occupational therapists in the country and found that 11% had lost their job due to the COVID-19 pandemic, with 38% of this group reporting that their institution had closed and 28.5% that their contract had not been renewed as result of lockdown changes. Reyes (2022) also highlights the levels of job insecurity experienced by occupational therapists in the country.…”
Section: Discussionmentioning
confidence: 99%
“…En el campo de la atención hospitalaria, los profesionales de las ciencias de la rehabilitación, apoyo diagnóstico y terapéutico, como lo son fisioterapeutas, terapeutas ocupacionales y fonoaudiólogos, han tenido que adaptarse y crear nuevas formas de abarcar no solo sus responsabilidades ya establecidas, sino también las que la pandemia ha traído consigo 6, 7 . Desde la rehabilitación, los equipos interdisciplinarios hacen frente a las distintas necesidades de los pacientes, quienes debido al COVID-19 pueden presentar dificultades respiratorias, desacondicionamiento físico y ocupacional, delirium, alteraciones cognitivas, trastornos de la deglución, comunicación e interacción social, así como otras afecciones posteriores, como las relacionadas con la ejecución de tareas cotidianas y la participación en actividades académicas o laborales 6,8-10 .…”
Section: Introductionunclassified